Relationships between starting block performance and dynamic strength index in elite sprinters - Cavaca, M. L.; Abrantes, J. M.; Valamatos, M. J. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: In short sprinting events like 100m race, performance at the starting block (SB) phase has a critical importance to the final outcome. Among different variables mentioned as critical of SB performance, normalized average horizontal power (NAHP) was identified as the most appropriate measure of performance [1]. This indicates that the athletes ability to produce horizontal power (HP) in a short period of time is a decisive factor in this phase of race. Thus, it is of great interest for strength and conditioning coaches who work with sprinters to understand the associations between athletes SB and their lower limbs strength and power qualities. We aim to understand the relationship between SB performance of elite male sprinters and their lower-body dynamic strength index (DSI).